The state of the art of Ceramonematidae (Nematoda, Leptolaimida): a historical review, diagnoses and lists of valid genera and species - Macedo, Rafaela; Venekey, Virág (Zootaxa, 2026)
Ceramonematidae is a family of exclusively free-living marine nematodes. This work addresses the state of the art and historical review of the group, providing lists of valid species, lists of species inquirendae and species nomina nuda, and updated diagnoses for each genus. Many species have only male or female specimens and some original illustrations are poorly detailed, making it difficult to compare species for new descriptions. Our review presents comparative tables of all species in each genus and ultimately recognizes 8 valid genera, 69 valid species, 2 species inquirendae, and 9 species nomina nuda.